Ancestral calling, traditional health practitioner training and mental illness: An ethnographic study from rural KwaZulu-Natal, South Africa. (August 2021) - van der Zeijst, Martine; Veling, Wim; Makhathini, Elliot Mqansa; Susser, Ezra; Burns, Jonathan K.; Hoek, Hans W.; Susser, Ida
This qualitative ethnographic study complements an epidemiological study on first episode psychosis in Vulindlela, a rural area in KwaZulu-Natal, South Africa. It focuses on two themes that emerged from our data: (1) the calling of the ancestors to become a traditional health practitioner and (2) ukuthwasa, the training to become a traditional health practitioner. The purpose of this study is to describe the ancestral calling, and to explore whether ukuthwasa may help with the management of mental disturbances, including unusual perceptual experiences. We also provide a discussion of the changing sociopolitical context of healing in KwaZulu-Natal, as a background to our study. In-depth interviews were conducted with 20 (apprentice) traditional health practitioners, formal health practitioners, patients and relatives recruited through local traditional health practitioners and a health care clinic. Our results show that the ancestral calling might announce itself with symptoms of mental illness including unusual perceptual experiences, for which some participants consider ukuthwasa as the only effective cure. We found indications that in some individuals successful completion of ukuthwasa might promote recovery from their illness and lead to a profession in which the unusual perceptual experiences become a legitimate and positively valued aspect. We suggest that – in this particular community today, which has been subject to several sociopolitical changes – ukuthwasa may be a culturally sanctioned healing process which moderates experiences that a Western psychiatric system might characterize as psychotic symptoms, providing some individuals with a lucrative and respected role in society.